Language as means and as an obstacle of communication. Phenomenological grounds for intercultural understanding - Dieter Lohmar (Enrahonar: Quaderns de Filosofia, 2016)
In this article I will establish the concept of a “symbolic system of representation” to make clear how it is possible that humans are not only using the language-based system of representation for cognitive contents. A system of representation should enable us to “think”, i.e. to form and manipulate an idea of a state of affairs or of an event without having the appropriate intuition of them. We believe that we do this mostly in language. My thesis is that there are non-linguistic systems of representation with the same performance. We simultaneously use different systems of representation; the most prominent are language, gestures, feelings, and scenic images. Phenomenological analysis reveals that it is especially fruitful to investigate into the scenic mode of daydreaming as a central form of non-linguistic thinking. By close comparison of non-linguistic systems of representation and non-linguistic communication, their common ground in similarity semantics is revealed. This is the principal basis to begin and maintain intercultural understanding across the borders of national languages.